The Thin Line between Real and Unreal. A Semiotic Approach toward AI-generated Content in the Fashion Domain - Alice Venturini (Ocula)
Nowadays the fashion advertising scenario is rapidly changing. The rise of new technologies has notably influenced the way the apparel industry produces, distributes, and communicates. Among these technologies we find Artificial Intelligence (AI). Despite its widespread adoption, however, semiotics research has yet to focus on the verisimilitude meanings conveyed by AI-generated ads. This paper aims to fill this gap by focusing on two forms of textuality that are challenging the contemporary notion of advertising, namely Computer-Generated Imagery (CGI) and Deepfakes. For each of these communication forms, a semiotic analysis will be undertaken. The two content will provide valuable insights on the capabilities of AI in generating verisimilitude meanings for fashion brands as well as on the growing empowerment of the consumer to appropriate the brandâs discourse, respectively. Implications for both theory and practice will be highlighted in the conclusion.